Dressing Barbie : a celebration of the clothes that made America's favorite doll, and the incredible woman behind them /: a celebration of the clothes that made America's favorite doll, and the incredible woman behind them. (2019) - Spencer, Carol; Brookins, Laurie
No abstract available